Kerjasama Perguruan Tinggi dalam Pembinaan Skill Mahasiswa : Literatur Review - Agus Yohana; Salihah Khairawati; Wijiharta Wijiharta; Muhajirin Muhajirin (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2021)
This literature review aims to determine the role of higher education cooperation, especially in efforts to improve student soft skills. A study of 53 selected literature produced some information on the benefits of university collaboration for student soft skills development, benefits for institutions, stages, patterns of cooperation, forms of cooperation activities, actors of cooperation, and obstacles that arise. The conclusion obtained is that the collaboration between universities and fellow universities, the business world and industry, the community, and the government will support the development of student skills. Universities also need to have a strategic plan related to cooperation so that the goals and targets of cooperation are more focused, thereby minimizing the emergence of obstacles both at the strategic and policy level, organizational and technical operations. Cooperation with strategic partners with the right agenda of activities is expected to have a better impact on increasing students' knowledge, hard skills, and soft skills.